PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT PERSADA HARDANA REVORMA DI JAKARTA SELATAN - Neila Rizky, Astrid; Ratnawati, Whina (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of motivation and work discipline on the performance of employees of PT Persada Hardana Revorma South Jakarta. The method used is quantitative. The sampling technique used saturated sampling and a sample of 60 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research simultaneously have a significant effect on employee performance with a regression of Y= 6.900 + 0.387 (X1) + 0.463 (X2), a correlation coefficient value of 0.786, a coefficient of determination (R square) of 0.786 (8.6%). Motivation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 6.900 + 0.387X1 + 0.463X2. The coefficient of determination value is 61.8% while the remaining 38.2% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (46.132 > 2.770).